The New South Wales Teachers Federation, the Conciliation Committee of 1927-1929, and the Formation of the Educational Workers League. Issue 2 (23rd January 2020) - Kass, Dorothy; Sullivan, Martin
Abstract : Purpose: Originally written in the 1990s but unpublished, the paper is now revised; the purpose of this paper is to examine the context of the formation of the Educational Workers League of NSW in 1931 with particular emphasis on the NSW Crown Employees (Teachers) Conciliation Committee and the enactment of its agreement in the worsening economic conditions of the Depression. The aims, reception and possible influence of the League on Federation policy and practice are addressed. Design/methodology/approach: Primary source material consulted includes the minutes of the Conciliation Committee's sittings from September 1927 to July 1929; papers relating to the Educational Workers League held in the Teachers Federation Library; and the Teachers Federation journal, Education . Findings: The Conciliation Committee's proceedings and outcomes had far reaching implications. The resultant salary agreement received a hostile reception from assistant teachers and fuelled distrust between assistants and headmasters. As economic depression deepened, dissatisfaction with the conservative leadership and tactics of the Federation increased. One outcome was the formation of the radical, leftist Educational Workers League by teachers, including Sam Lewis, who would later play key roles within the Federation itself. Originality/value: While acknowledging the extensive earlier work of Bruce Mitchell, the paper contributes to a deeper understanding of teacher unionism and teacher activism in the 1920s and 1930s. Apart from brief attention by Federation historians in the 1960s and 1970s, there has been no history of the formation, reception and significance of the Educational Workers League.